2011
DOI: 10.1007/s11845-011-0755-8
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume predicting carotid atherosclerosis in atherothrombotic ischemic stroke

Abstract: Our results indicate that an elevated MPV could be an easily measurable marker of severity of carotid stenosis in patients with atherothrombotic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 23 publications
6
29
0
Order By: Relevance
“…These mediators can contribute to inflammation and atherogenesis and may explain the association between MPV and atherosclerosis. It has been previously shown that larger platelets are associated with severity of CAD [31], PAD [32][33], and carotid atherosclerosis [34][35]. Possible mechanism for correlation of larger platelets with ischemic stroke as shown in our study may be the augmented rate of atherosclerosis unlike atrial fibrillation or other prothrombotic conditions.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These mediators can contribute to inflammation and atherogenesis and may explain the association between MPV and atherosclerosis. It has been previously shown that larger platelets are associated with severity of CAD [31], PAD [32][33], and carotid atherosclerosis [34][35]. Possible mechanism for correlation of larger platelets with ischemic stroke as shown in our study may be the augmented rate of atherosclerosis unlike atrial fibrillation or other prothrombotic conditions.…”
Section: Discussionsupporting
confidence: 65%
“…The relationship between increased platelet activity and atherosclerotic disease, including stroke, has been well documented [6][7][8]. It has been shown that high MPV is associated with an increased risk of stroke [9] and is an independent risk factor for stroke [10] in patients with atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…However, until this issue in which Kalkan et al (4) entitled “Mean platelet volume is associated with aortic intima-media thickness in patients without clinical manifestation of atherosclerotic cardiovascular disease.” published in Anatol J Cardiol 2015; 15: 753-8 report an association between MPV and the extent of subclinical thoracic aortic atherosclerosis in patients without a clinical manifestation of atherosclerotic cardiovascular disease, we did not know the role of this potential marker in the general population without cardio-vascular events, namely, in people whose prothrombotic status is unknown or supposedly inactivated. The authors showed how the extent of thoracic aorta intima to media thickness, as a marker of diffuse atherosclerotic disease, is significantly related to an increasing MPV, supporting the role of systemic thrombocyte activation over the course of atherosclerosis, a relationship that has been previously reported, though in a different scenario such as coronary or carotid arteries (5) and again, in patients with atherosclerotic disease present.…”
supporting
confidence: 69%
“…In many adult studies, MPV is increased in atherosclerotic disorders (10,11 There are studies reporting incidence of NP as 25% in patients with allergy and the frequency of allergic rhinitis as 10-54% in patients with NP (3). It was reported that rate of allergic rhinitis is about 10-30% in general population and raises up to 45% in children (12).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are studies about the relationship between atherosclerosis and NP or MPV, there is no study focusing directly on the relationship between NP and MPV according to our knowledge (7,8,10,11).…”
Section: Introductionmentioning
confidence: 99%